The Contribution of Genre to Translation Process & Product: Feature Texts - Nadia Gitya Yulianita; Novita Sumarlin Putri (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
This paper aims to investigate how genre is used to help the translator analyze, understand, and translate feature articles from English to Indonesian and the differences in the convention of feature article in other languages. The genre approach is used to give a brief understanding in analyzing the feature article. In this research, the researchers use the ESP (English for Specific Purposes) which sees that genre has the consistency of communicative purpose. Moreover, this research uses parallel texts in the Indonesian version to compare with the English version to know the convention of feature article. The result shows that genre approach, especially ESP, helps the translator overcome the problems in translating feature articles since genre can show the convention, communicative purpose, formulaic expressions, dictions, discourse strategy, discourse community, and discourse markers of the texts. Thus, the translator can find proper translations to fit those criteria.